(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
With the purpose of education, traveling of people interested in“Educational Tourism” dates back to the earlier past where the Caucasus in general and Georgia took their special place. The first quarter of the 20th century saw the rising interest of European countries and Russia towards the Caucasus and Georgia from the point of tourism. For educational purposes people used to arrive here individually or in groups in order to satisfy their scientific interest. Those people mainly came from Poland, Germany, Moscow, St. Petersburg, Ekaterinoslav, Kiev, etc. In the Caucasus and Georgia the educational-cognitive, scientific tours were held under the consent and the patronage of government authoritative officials. Tour participants’ interest covered unique diversity of the nature, flora, fauna, architecture of historical monuments both in mountains and valleys. Also the ethnic composition of the inhabitants from the geopolitical area, their traditions, culture, peculiarities, religious denominations and others were the subjects of their interest.